Q. 25

Sums of

Answer :


Let x be the first term and d the common difference.

Sp = p/2[ 2x + (p-1)d] = a

Sq = q/2[2x + (q-1)d] = b

Sr = r/2[2x + (r-1)d] = c

2x + (p-1)d = 2a/p………..(i)

2x + (q-1)d = 2b/q………..(ii)

2x + (r-1)d = 2c/r………….(iii)

Eliminating x and d from (i), (ii) and (iii).

(p-q)d = 2a/p - 2b/q [Subtracting (i) and (ii)] ……(iv)

(q-r)d = 2a/q - 2c/r [Subtracting (iii) and (ii)] … (v)

[ Dividing (iv) and (v)]

=

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses